Fatty Acid Optimization of Locally Produced Ready-to-Use Therapeutic Foods for the Treatment of Acute Malnutrition in Children Using Linear Programming: An Application to India and Pakistan. - Ismail, Samir; Umesh, Amith; Khan, Mohid; Moutwakil, Ahmed; Nguyen, Tu; Dantuluri, Meghana; Annadanam, Akhila; Prasad, Ayush; Multra, Melody; Sudhakar, Deepti; Mahadevan, Varun; Khan, Gul Nawaz; et al. (Nutrients, 2025)
Background/Objectives: Ready-to-use therapeutic foods (RUTFs) are a common treatment for children under five years diagnosed with acute malnutrition. However, traditional RUTFs are often not locally produced, and the costs of the RUTF can be a barrier to access in India and Pakistan. Our goal was to utilize linear programming (LP) to generate an RUTF formulation based on ingredients locally available in India and Pakistan. We also aim to evaluate the effectiveness of LP in generating such a recipe that is also nutrient-optimized to promote neurocognitive recovery. Methods: The RUTF recipe was generated by applying linear programming to a database of crop ingredients available in India, subject to nutritional constraints. The resulting formulation was produced and evaluated for nutrition content and shelf life. The efficacy of the LP tool was also evaluated based on the formulated product. Results: We demonstrate that the linear programming tool is largely accurate in predicting the true nutritional content of the formulation. Furthermore, the generated formulation, per 100 g, meets many global macronutrient standards for RUTFs while maintaining a predicted cost that is lower than that of industry-standard products. The conducted shelf-life study indicates the viability of the RUTF throughout an accelerated testing period. In addition, the satisfactory consideration of LA and ALA levels provides our RUTF with the potential to address concerns about low DHA levels, and thereby cognitive health, as compared to traditional RUTFs. Conclusions: We use linear programming to generate an affordable and fatty acid-optimized RUTF based on locally available ingredients. Therefore, this formulation holds immense potential to benefit communities in India and Pakistan facing high levels of child malnutrition.